Factors associated with maternal deaths in Cotonou hospitals, Benin - AGUEMON, BADIROU DIN OWOLADÉ OTONIKOU; Damien Barikissou, Georgia (My University, 2023)
Background: Maternal mortality remains a major public health issue in Benin. The aim of this study was to determine the hospital-based maternal mortality ratio and factors associated with maternal deaths in Cotonou. Subjects and Methods: We conducted a case-control study over a two-year period from 1st January 2020 to 31 December 2021 in four Cotonou hospitals. It included 264 maternal deaths (case) matched to 264 controls by delivery mode. The dependent variable was the status at discharge. Independent variables included socio-demographic characteristics, and gyneco-obstetric informations, medical and gynecologic history as well as type of complications. Univariate and multivariate analysis were performed to identify the factors associated to maternal deaths. Results: The hospital-based maternal mortality ratio was 1403 deaths per 100,000 live births. Age superior than or equal to 30 years old (OR= 3.09 ; CI 95%: 1.52 to 6.41 ; p=0.002), admission by a referral from public health facility (OR=4.26, CI95% :2.60-7.10 ; p<0.001) or private health facility (OR=4.52, CI95% :2.49-8.38 ; p<0.001); parity between 1 and 3 (OR=2.72, CI95% :1.27-6.15 ; p=0.012), gestational age less than or equal to 31 weeks (OR=3.77 ; CI95% : 2.13-6.84 ; p<0.001) and the occurrence of non-infectious (OR=1.94 ; CI95% : 1.27-2.97 ; p=0.002) and fetal (OR=1.98 ; CI95% : 1.13-3.54 ; p=0.018) complications were the factors associated to maternal deaths. Conclusion: Strengthening policies aiming to increase access to modern methods of contraception and safe abortion, improving the referral system and implementing multifaceted contextualized interventions could contribute to reduce maternal mortality.
Keywords: Maternel death; maternal mortality; associated factors; Benin